Pengaruh Metode Qiraati terhadap Kemampuan Membaca al-Qur’an Siswa SMP IT Insan Sejahtera - Wahidah, Haerani; Hadiana, Eri (Yayasan Cendekia Gagayunan Indonesia, 2024)
This study is motivated by the lack of teacher creativity in delivering the material, some students are less careful in paying attention to makharijul letters and tajweed rules, and the lack of parental awareness in motivating students, causing students' ability to read the Qur'an to be hampered and less than optimal. This study aims to determine the extent to which the Qira'ati method affects the ability to read the Qur'an. This type of research is quantitative research with a descriptive approach. The location studied was SMPIT Insan Sejahtera. The sample in this study were all finishing class students totaling 32 people. While the sampling technique uses population sampling technique that is taking the whole of the population. Data collection was carried out using the questionnaire method. The analysis technique used is simple linear regression analysis, from hypothesis testing in research using the t test. The results of the research conducted by the researcher, managed to obtain data on the results of the influence of the Qira'ati method on the ability to read the Qur'an.